Long QT syndrome in a neonate - Rodríguez Balderrama, Isaías; Morales Rodríguez, Idelma Berenise; Rodríguez Martínez, V.; Rodríguez Bonito, Rogelio (UANL. Facultad de Medicina, 2015)
Congenital long QT syndrome (cLQTS) is a channelopathy characterized by ventricular repolarization disturbances. The clinical presentation varies from an asymptomatic patient to a patient with recurrent syncopes, seizures, and even sudden death. This article aims to contribute to medical knowledge of this relatively new disease in newborns, so that early diagnoses with timely treatments can be made. Genotypically, there are 13 types of cLQTS, which are classified by phenotype into: Romano-Ward, Jervell-Lange-Nielsen, Andersen-Tawil and Timothy. We present the following case of a newborn who presented clinical sustained bradycardia on her first day of life, who was admitted to the Neonatal Intensive Care, where her assessment and imaging studies guided us to a cLQTS diagnosis. The patient recovered satisfactorily, and was discharged with outpatient follow-up without complications. All abnormal QT patients should be assessed with an integral clinical report, Holter analyzer, and a stress test. Ideally, a genetic screening, which can have a great impact on the treatment, should be done. Although it is relatively uncommon, recognition of this entity is important because it can prevent death. We present a case of cLQTS diagnosis, with approach and treatment.